Amelioration of Experimental Autoimmune Uveoretinitis by Aldose Reductase Inhibition in Lewis Rats - Yadav, Umesh C. S. (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. Recently, the authors showed that the inhibition of aldose reductase (AR) prevents bacterial endotoxin-induced uveitis in rats. They have now investigated the efficacy of AR inhibitors in the prevention of experimental autoimmune-induced uveitis (EAU) in rats. METHODS. Lewis rats were immunized with bovine interphotoreceptor retinoid-binding peptide (IRBP) to develop EAU. Two or 8 days after immunization, the rats started receiving the AR inhibitor fidarestat (7 mg/kg/d; intraperitoneally). They were killed when the disease was at its peak; aqueous humor (AqH) was collected from one eye, and the other eye of each rat was used for histologic studies. The protein concentration and the levels of inflammatory markers were determined in AqH. Immunohistochemical analysis of eye sections was performed to determine the expression of inflammatory markers. The effect of AR inhibition on immune response was investigated in isolated T lymphocytes. RESULTS. Immunization of rats by IRBP peptide resulted in a significant infiltration of leukocytes in the posterior and the anterior chambers of the eye. Further, EAU caused an increase in the concentration of proteins, inflammatory cytokines, and chemokines in AqH, and the expression of inflammatory markers such as inducible-nitric oxide synthase and cycloxygenase-2 in the rat eye ciliary bodies and retina. Treatment with fidarestat significantly prevented the EAU-induced ocular inflammatory changes. AR inhibition also prevented the proliferation of spleen-derived T cells isolated from EAU rats in response to the IRBP antigen. CONCLUSIONS. These results suggest that AR could be a novel mediator of bovine IRBP-induced uveitis in rats.